Blockchain fundamentals for Web 3.0 - Lacity, Mary C., ....-; Lupien, Steven C., ....- (Arkansas : Epic Books, 2022)
Our book explains the movement to establish online trust through the decentralization of value, identity, and data ownership. This movement is part of 'Web 3.0', the idea that individuals rather than institutions will control and benefit from online social and economic activities. Blockchain technologies are the digital infrastructure for Web 3.0. While there are many books on blockchains, crypto, and digital assets, we focus on blockchain applications for Web 3.0. Our target audience is students, professionals, and managers who want to learn about the overall Web 3.0 landscape--the investments, the size of markets, major players, and the global reach--as well as the economic and social value of applications. We present applications that use Web 3.0 technologies to unlock value in DeFi, NFTs, supply chains, media, identity, credentials, metaverses, and more. Readers will learn about the underlying technologies, the maturity of Web 3.0 today, and the future of the space from thought-leaders. This textbook is used by undergraduate and graduate Blockchain Fundamentals courses at the University of Arkansas, the University of Wyoming, and other universities around the world. Professors interested in adopting this book for instructional purposes are welcome to contact the authors for supporting instructional materials.
Keywords: Blockchain